Ways to Use Text Issues When Cultivating Students ' Thinking Skills - Rakhmonkulova Nafisa Khasanovna; Mirzanazarova Shukurona Avazbek qizi (Researchparks Publishing, 2022)
Solving textual issues the formation of excellent mathematical concepts in children first of all is important in the development of students ' thinking skills, along with the assimilation of their theoretical knowledge, which is determined in the program. For example: if we want to form a correct understanding of addition in students, for this it is necessary that children solve a sufficient number of simple issues related to finding the sum, almost every time following the action of combining sets. For example: the following issue is given.